VERBAL HUMOUR AND ITS TRANSLATION STRATEGIES IN THE INDONESIAN SUBTITLES OF UNFROSTED FILM - Valentina Irfanti Pingga; Restu Arini (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study examines the types of verbal humour and their translation strategies in the Indonesian subtitles of the film Unfrosted. This study uses a descriptive qualitative method to analyze 30 dialogue samples containing verbal humour expressions. The results of this study indicate six types of verbal humour out of the twelve types identified in Shade's theory (1996). The findings of this study reveal six types of verbal humour out of the twelve types identified in Shade's theory (1996). The most frequent type is wit, followed by sarcasm and satire, while irony, parody, and farce are the least frequent, with only one occurrence each. This study also identifies four out of ten translation strategies from Gottlieb's theory (1991) applied in the film, with paraphrase being the most dominant, followed by condensation and transfer, and the least frequent expansion strategy, which is two times. This study concludes that studying various types of verbal humour is very important because there are multicultural differences in conveying humorous meanings. This study emphasizes that various translation strategies must successfully maintain the meaning of humour. This study provides valuable insights into the field of linguistics, into the types of verbal humour and translation strategies in film subtitles. Keywords: Verbal humour; translation strategies; subtitling; audiovisual translation;                  linguistics